Personal Hygiene and Soil Transmitted Helminth (STH) Infection in Rice Farmers in East Bulotadaa Village, Gorontalo City - Siti Fadya Az’zahra Alamri; Herlina Jusuf; Tri Septian Maksum (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Soil Transmitted Helminth (STH) infections are still a public health problem, especially in occupational groups that have direct contact with the soil such as rice farmers. A humid and muddy rice field environment and a lack of personal hygiene can increase the risk of worms. The purpose of the study was to determine personal hygiene and STH infection in rice farmers in East Bulotadaa Village, Gorontalo City. Types of quantitative research with a descriptive survey approach. The research sample of 38 rice farmers was selected using the purposive sampling technique. Personal hygiene data and health complaints were obtained through interviews, the identification of worm eggs was carried out through laboratory examination using the flotation method on farmer nail samples. The results of the personal hygiene research on farmers did not meet the requirements as many as 34 respondents (89.5%). Poor hand washing habits were 27 respondents (71.1%), poor nail cutting habits were 35 respondents (92.1%), and poor use of gloves and footwear were 30 respondents (78.9%). Laboratory examination, 14 respondents (36.8%) were positive for STH worm eggs and 24 respondents (63.2%) were negative. The eggs of the worms found include Ascaris lumbricoides, Trichuris trichiura, and Hookworm. A total of 18 respondents (47.4%) experienced health complaints such as itching of the skin, diarrhea, weakness and easily broken nails. In conclusion, most rice farmers have poor personal hygiene and STH infection is still found on the farmers' nails. It is recommended to improve personal hygiene by getting used to washing hands with soap, cutting nails, and using personal protective equipment to prevent worms.